Profitability's Impact on Tax Avoidance in IDX-Listed Energy Firms (2021–2023 Study) - Noviana, Endah Siti; Masruri, Fahrul Alam; Kartika, Tita (LPPM Universitas Sebelas April, 2025)
This study aims to see the Effect of Profitability on Tax Avoidance (Empirical Study of Oil, Gas and Coal Sub-sector Energy Companies Listed on the IDX in 2021 - 2023). This study uses a quantitative research method. The population in this study is the Oil, Gas and Coal Sub-sector Energy Companies Listed on the IDX in 2021 - 2023. The sample selection method used in this study is the purposive sampling method, where there are 10 oil, gas and coal sub-sector energy companies that meet the sample criteria with a 3-year observation method. The analysis methods used in this study include descriptive statistics, classical assumption tests (normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests), multiple linear regression analysis, hypothesis tests (t-tests and f-tests), and determination coefficient tests. Based on the test results, it shows that profitability (Return On Asset) with partial ETR measurement has no significant effect on tax avoidance as evidenced by the significance value of 0.420> 0.05 and the calculated t value <t table, which is -0.818 <2.051, so H1 is rejected. Profitability (Return On Equity) with partial ETR measurement has no significant effect on tax avoidance as evidenced by the significance value of 0.683> 0.05 and the calculated t value <t table, which is -0.413 <2.051, so H1 is rejected. Simultaneously, profitability (ROA and ROE) have a significant effect on tax avoidance with measurement using ETR as evidenced by the resulting sig value of 0.005 <0.05 and Fcount> Ftable, which is 6.467> 3.35, so H1 is accepted. This means that partially ROA and ROE on tax avoidance do not have a significant effect on oil, gas and coal sub-sector energy companies listed on the IDX in 2021-2023. While simultaneously profitability (ROA and ROE) on tax avoidance has a significant effect on oil, gas and coal sub-sector energy companies listed on the IDX in 2021-2023.